Intermediate-Term Precursors of Large (M ≥ 6.6) Kamchatka Earthquakes for the Period from 1987 to 2004: A Retrospective Assessment of Their Information Content for Prediction - Serafimova Yu.K.; Kopylova G.N. (My University, 2010)
Data from the literature were used to systematize intermediate-term (with advance times of 1 month to ~2.5 years) precursors to the M ≥ 6.6 Kamchatka earthquakes of 1987−2004. The precursors were observed as changes in seismological, geodetic, geophysical, water-level, and hydrochemical parameters. Retrospective assessment of the information content in these intermediate-term precursors for earthquake prediction is in progress. The focus was on estimating the occurrence times of various precursors as functions of earthquake parameters (magnitude M, hypocentral distance R, and epicenter location). In the conditions of the Kamchatka observing network, precursors can be identified by a combination of methods, mostly before M ~ 7 earthquakes or greater south of the Kronotskii Peninsula, for which It is shown that the relative proportion of earthquakes for which precursors have been identified in the observations considered here is 0.43–0.86.
Keywords: 37.31.19 Сейсмология